1987
DOI: 10.1536/ihj.28.891
|View full text |Cite
|
Sign up to set email alerts
|

Potency and receptors involved in coronary vasoconstriction caused by neuropeptide Y(NPY).

Abstract: SUMMARYUsing anesthetized dogs, the coronary vascular effects of neuropeptide Y (NPY) were studied and the action of alpha-or serotonergic receptor blockade on the action of NPY was evaluated.To demonstrate the biological significance of the action of NPY, the vasoconstrictor potencies of NPY and norepinephrine were compared. One to 5 nmol of intracoronary NPY reduced coronary flow in a dose-dependent manner.The action started rather gradually and lasted for 10 min or more. Since perfusion pressure and central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Strong vasoconstriction in the presence of NPY is observed in the coronary arteries from many species including humans, and the primary effect is localised in the small arteries [79,80], the result of a direct effect on vascular smooth muscle [81,82]. NPY can potentiate the effects of various mediators, including NE, histamine, 5-hydroxytryptamine, angiotensin II, prostaglandin F 2 and endothelin-1, on vascular tone [83], in some cases through an endothelium-dependent mechanism [84].…”
Section: Biological and Pathological Effects Of Npy In The Heartmentioning
confidence: 99%
“…Strong vasoconstriction in the presence of NPY is observed in the coronary arteries from many species including humans, and the primary effect is localised in the small arteries [79,80], the result of a direct effect on vascular smooth muscle [81,82]. NPY can potentiate the effects of various mediators, including NE, histamine, 5-hydroxytryptamine, angiotensin II, prostaglandin F 2 and endothelin-1, on vascular tone [83], in some cases through an endothelium-dependent mechanism [84].…”
Section: Biological and Pathological Effects Of Npy In The Heartmentioning
confidence: 99%
“…These latter direct effects appear to depend on high local concentrations of NPY and are most easily observed in the rat (see also Zukowska-Grojec et al, 1987). More recently, experiments performed on anaesthetized dogs have shown that local injection of NPY into coronary arteries will cause a local vasoconstriction (Aizawa et al, 1987;Martin & Patterson, 1989) or a reduction in coronary blood flow (Allen et al, 1986;Maturi et al, 1989) but effects on contractility are variable (Allen et al, 1986;Martin & Patterson, 1989). A decrease in contractility has been observed following intravenous injection of NPY in the anaesthetized rabbit (Minson et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…2 NPY causes considerably more long-lasting coronary vasoconstriction than NE. 19 A recent study demonstrated that NPY, released from cardiac sympathetic nerves during electrical nerve stimulation in dogs, 4 participates in the elicitation of a long-lasting coronary vasoconstriction. This may be of interest in consideration of the maintained ischemia in the recovery phase.…”
Section: Possible Role Of Npy In Ischemiamentioning
confidence: 99%